Fluoxetine attenuates stress-induced depression-like behavior due to decrease in pro-inflammatory cytokines in male rats. - Nabirumbi, Ritah; Onohuean, Hope; Kato, Charles Drago; Alagbonsi, Abdullateef Isiaka; Adedeji1, Ahmed A. (2024)
Pro-inflammatory cytokines are implicated in depression caused by both environmental- and alcohol-induced stress. The purpose of the study was to investigate the cytokine levels in serum and hippocampus following induction of depression-like behaviors (DLB) by either force. swimming test (FST) or ethanol-induced DLB (EID). We also investigated the effect of prior administration of the antidepressant drug fluoxetine on cytokines in animals exposed to both models of DLB. Methods: Animals were pretreated with fluoxetine before inducing DLB, while DLB was induced in some animals using FST and ethanol in different groups of rats without fluoxetine pretreatment. The ELISA was used to detect changes in cytokine (IL-1β, IL-6, and TNF-α) levels in serum and hippocampus. Results: The mean levels of IL-1β and IL-6 measured in serum and hippocampus were significantly higher in FST and EID models when compared to the control group. The serum concentrations of IL-1β and IL-6 were significantly reduced in animals pre-treated with 5 mg/kg and 10 mg/kg of fluoxetine in both FST and EID models when compared to the untreated FST and EID groups respectively. Conclusions: In conclusion, both environment and alcohol can induce stress and DLB in rats with similar intensity, and their mechanisms of DLB induction involve activation of pro-inflammatory cytokines. Moreover, fluoxetine can prevent stress-induced inflammation in models of DLB.